The subculture of clothing between human rights and the threat of terrorism - Spasojević, Đorđe; Prelević, Plavšić; Vlajnić, Jelena (Pravo, teorija i praksa, 2025)
Although at first glance clothing choices appear to be a matter of individual freedom-subject only to certain exceptions involving unwritten, or more rarely written, norms that typically carry no serious sanctions-there are situations in which this issue is raised to a much higher level. It is often linked to specific garments associated with Muslim women, such as the hijab, niqab, burqa, and others. In line with this, the paper highlights certain challenges related to human rights issues, but also to security concerns, which require a more in-depth and nuanced approach, especially considering numerous instances in which men dressed as women have carried out terrorist attacks or evaded law enforcement. In order to propose a suitable legal solution-a compromise that would respect individual rights while also addressing potential security risks-the paper employs several methodological approaches. A comparative method is used to examine the legal frameworks of different countries. Documentary analysis is applied to judgments of the European Court of Human Rights. Additionally, an analytical approach is used to examine relevant passages from the Qur'an that pertain to clothing and the obligation to cover certain parts of the body.